On the Centrality and Significance of Stimulus-Encoding Deficit in Schizophrenia - Neufeld, Richard W. J. (Oxford University Press, 2007)
Increased latency of stimulus encoding is presented as a central deficit in schizophrenia cognition. Encoding, here, entails the internal representation of presenting stimuli in a format facilitating their implementation in other cognitive processes, such as those taking place in working memory. Historical roots of suspected encoding debility in schizophrenia briefly are reviewed, and its singular empirical robustness is described. More recently, this deficit has been subjected to stochastic mathematical modeling, resulting in its decomposition into discrete cognitive functions. A nonmathematical exposition of this account is provided, and substantial behavioral study support is illustrated. Implications for clinical assessment of individuals and of treatment regimens, with respect to encoding-related cognitive efficiency, are noted. Finally, because stochastic dynamic trajectories of process duration are modeled, times of measurement interest, complementing neuroanatomical regions of interest, become available for enhanced temporal navigation of event-related fMRI. Results from recent implementations of such process-defined events are described.